PENGARUH TERAPI JUS PEMENGKUR (PEPAYA MENGKAL DAN KURMA) TERHADAP PENURUNAN TEKANAN DARAH - Septiana Anjora; Erwin Erwin; Juniar Ernawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
This study aims to determine the effect of juice therapy pemengkur juice (unripe papaya and wat dates) on blood pressure drop in patients with primary hypertension in the area of Limapuluh Health Center Pekanbaru. The method of the research is Quasy Experiment with non-equivalent control group design. The study involved 34 respondents consisting of 17 respondents in the experimental group and 17 respondents in the control group, fulfilling the inclusion criteria and it was taken by using purposive sampling technique. The instruments utilized were tension meter (Sphygmomanometer) and stethoscope. In this research, Univarite and bivariate analyses were applied by implementing Wilcoxon and Mann Whitney tests. The results showed the differences in mean of blood pressure before and after consuming pemengkur juice in the experimental group with p value of systolic (0.001) and p value of diastolic (0.000), in conclusion p value < (α=0,05). The results of this study recommend people to administer papaya juice and wet dates as one of fruits that can be used to lower high blood pressure. Keywords: Primary hypertension, unripe papaya (carica papaya), wet dates (phoenix dactylifera)